PEWARISAN NILAI-NILAI DAN BUDAYA DALAM PENDIDIKAN ISLAM - Basnang Said (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
Islam is a perfect religion as stated in the Holy Qur’an and the Prophetic Traditions. The Qur’an and the Prophetic Tradi-tions are the foundation of Islamic education. Nevertheless, education keeps on changing along with social condition. Faster social change will result in cultural lag. This paper discusses the values and culture which may be inherited to and the role of Islamic education to trans-mit them. There are three important aspects to impart to the next ge-neration. These are 1) belief in the unity of God, 2) Islamic law, and 3) character. Islamic education plays an important role to impart these aspects in the three centre of education: the family, school and com-munity.